IMPLEMENTING HABITUATION IN STUDENTS’ CHARACTER BUILDING AT SD INPRES ANDI TONRO MAKASSAR - Mirna Sari Siradjuddin; Abdul Azis Muslimin; Muhammad Akhir (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to reveal the implementation of habituation in students’ character building, to find out the students’ character, and to find out the supporting and inhibiting factors for the implementation of habituation on the students’ character. The method of this research was a descriptive method with a qualitative approach. The findings revealed that SD Inpres Andi Tonro had implemented various kinds of habituation to build the five main character values in the 2013 curriculum, namely: (a) Religious, (b) Nationalism, (c) Independent, (d) Cooperation, and (e) Integrity. The habituation in the students’ character building at SD Inpres Andi Tonro Makassar was implemented through routine programs. The school activity program had been planned before the new academic year began. The students’ activity program was well organized. Moreover, the habituation carried out every day also had a good impact on the students’ character because it was getting better than before. However, some students still did not have good character. This was due to various obstacles, including students’ different backgrounds, lack of parents’ attention, the unfavorable environment, the teachers’ limitations in controlling students at home, and students bringing smartphones to school. Apart from the obstacles, there were also some supporting factors, such as government support for character education, adequate human resources, complete school facilities and infrastructure, and extracurricular activities.